2020
DOI: 10.1136/archdischild-2019-317256
|View full text |Cite
|
Sign up to set email alerts
|

Examining which clinicians provide admission hospital care in a high mortality setting and their adherence to guidelines: an observational study in 13 hospitals

Abstract: BackgroundWe explored who actually provides most admission care in hospitals offering supervised experiential training to graduating clinicians in a high mortality setting where practices deviate from guideline recommendations.MethodsWe used a large observational data set from 13 Kenyan county hospitals from November 2015 through November 2018 where patients were linked to admitting clinicians. We explored guideline adherence after creating a cumulative correctness of Paediatric Admission Quality of Care (cPAQ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

7
2

Authors

Journals

citations
Cited by 25 publications
(34 citation statements)
references
References 26 publications
0
34
0
Order By: Relevance
“…In addition to the hospital level factors like laboratory and guideline availability, clinician level factors may also affect antibiotic prescription. Level of training and clinical experience is crucial in decision making and guideline adherence ( Ogero et al, 2020 ). Most of the hospitals in our study were internship training centres.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the hospital level factors like laboratory and guideline availability, clinician level factors may also affect antibiotic prescription. Level of training and clinical experience is crucial in decision making and guideline adherence ( Ogero et al, 2020 ). Most of the hospitals in our study were internship training centres.…”
Section: Discussionmentioning
confidence: 99%
“…Information Network 3 which has been collected over time from a number of referral hospitals now exist in Kenya and it has been used to answer a number of salient clinical questions relevant across a range of resource-limited setting. [71][72][73] Future studies on prognostic research should leverage such datasets to externally validate competing models identified in this review for comparative performances as recommended by Collins and Moons 74 and if necessary, predictive performance of such models should be improved by addition of new prognostic factors. We also noted that most of the included models simplified the original predictor coefficients by rounding them to a nearest integer.…”
Section: Open Accessmentioning
confidence: 99%
“…In consequence, the situation now, and one that will likely persist for many years, is that most inpatient paediatric and neonatal care in Kenyan county government hospitals is provided by prelicensure or 'intern' medical and non-physician clinician graduates (the latter have 3 years diploma training), who are under the supervision of junior general medical officers. 23 Walk-in paediatric outpatient care in county hospitals and all smaller public facilities is typically provided by clinical officers and nurses. In the public sector, therefore, the limited numbers of paediatricians and their resource-poor environments means their major practical role is oversight of care initiated, continued and provided by more junior professionals.…”
Section: Global Child Healthmentioning
confidence: 99%